Double Right Coronary Artery Originating From Separate Ostia in an Older Female Cadaver With Cerebrovascular Disease: A Case Report - Paige O'Brien Daly; Rachel Thomas; Makenzie Cree; Tierra Kindred; Selena Anand; Paul Foretich; Mishalle Rashid; Tiffany L. Carpenetti (Annals of Internal Medicine: Clinical Cases)
This case report presents an extraordinary finding: a double right coronary artery with each artery originating from separate ostia off the aorta. This case was discovered in the cadaver of a 76-year-old woman whose cause of death was cerebrovascular disease. We discuss the diagnostic intricacies and implications of this unique anomaly, emphasizing its rarity in reported cases, particularly in the circumstances of gender distribution and ostial origins.